[Aerial view of Cal Poly campus] (1975)
Aerial view of Cal Poly main campus, North Mountain, Red Brick Dormitories, Sierra Madre, Yosemite, Administration, University Union, Engineering East, Engineering West, Science Building, Dexter Library, Spanos Stadium, Agricultural Engineering - looking south